0287 Motivated Performance While Sleep Deprived: Neurobehavioral Correlates of Attentional Effort Deployment. (27th May 2020) - Massar, S A; Lim, J; Sasmita, K; Chee, M W
Abstract: Introduction: Sleep deprivation (SD) has a negative impact on the motivation to exert effort. This may contribute to the decline in attentional performance observed under SD. In this study we examined how SD affects motivated performance and effort-based decision making. Particularly, we used functional magnetic resonance imaging (fMRI) to uncover the neural mechanisms underlying the interplay between SD and motivated behavior. Methods: Twenty-seven healthy subjects were tested once after a night of sleep in the lab (9h Time in Bed; Rested Wakefulness = RW), and once after a night of total sleep deprivation (SD). Participants performed an effortful attention task with different incentive levels (0, 10, or 50 cents/fast and correct response). Behavioral performance and fMRI data were collected during task performance. Subsequently, participants performed an effort-based choice task, during which they could choose to earn additional rewards for performing the attention task for a longer duration. Results: As expected, attentional performance was worse in the SD session compared to the RW session. In addition, performance improved as a function of incentive level both in the RW and the SD session. This reward-effect was accompanied by increased activation in attention-related brain areas, and increased arousal-related thalamus activation. This reward-modulation was more extensive during RW than SD, particularly in the anterior cingulate cortex (ACC) and anterior insula (aIns; both areas involved in effort regulation). Results from the decision making task were less willing to perform the attention task for a further duration after SD compared to RW. Conclusion: Results show that performance decline after SD is reward-dependent and willingness to perform is reduced. Reward modulation of attention-related brain activation is reduced, particularly in areas that are associated with effort regulation (i.e. ACC and aIns). These findings indicate that motivational factors contribute to decline of vigilance following sleep deprivation. Support: This work was supported by grants awarded to Dr. Michael Chee from the National Medical Research Council (NMRC/STaR/0015/2013), and the Far East Organization.